La compétence discursive au croisement de la médiation intralinguistique et de la compétence grammaticale : exemple de transposition d’un dialogue en texte narratif - Grabowska, Monika (Studia Romanica Posnaniensia, 2017)
The aim of the paper is to study the impact of the instruction, focused either on the grammatical component (the indirect speech) or the discursive component (the transformation of a dialogue into narration) of the communication competence on the quality of intralinguistic mediation carried out by learners at higher levels of competence (from B2). We argue by the divergence between the productions resulting from the first and the second instruction a need to ensure a didactic transition from the exercise of indirect speech (work on form) to its actual discursive use (social practice), according to the principles of the action-oriented approach.